Genre in English medical writing, 1500-1820 sociocultural contexts of production and use - Taavitsainen, Irma 1946-; Hiltunen, Turo ca. 20./21. Jh; Smith, J. J. 1955-; Suhr, Carla 1973- (Studies in English language, 2022)
Written by an interdisciplinary team of scholars, this book offers novel perspectives on the history of medical writing and scientific thought-styles by examining patterns of change and reception in genres, discourse, and lexis in the period 1500-1820. Each chapter demonstrates in detail how changing textual forms were closely tied to major multi-faceted social developments: industrialisation, urbanisation, expanding trade, colonialization, and changes in communication, all of which posed new demands on medical care. It then shows how these developments were reflected in a range of medical discourses, such as bills of mortality, medical advertisements, medical recipes, and medical rhetoric, and provides an extensive body of case studies to highlight how varieties of medical discourse have been targeted at different audiences over time. It draws on a wide range of methodological frameworks and is accompanied by numerous relevant illustrations, making it essential reading for academic researchers and students across the human sciences